Hardwired: and other tales of Gothic reflection - Antenucci, Marilyn Kathleen, author; Morales, Juan, advisor; Eskew, Douglas, committee member; Souder, Donna, committee member (Colorado State University. Libraries, 2012)
Hardwired: And Other Tales of Gothic Reflection is a short story collection that mirrors the writer's fascination with Gothic's anxiety over the past haunting the future. As we endeavor to grasp the significance of our own lifetime, we also strive to rectify our temporal position in relation to past and future generations. Hardwired recognizes that our physical bodies and the emotions hardwired into our psyche come from a deep ancestral inheritance. While our lives remain a product of the past, the ways in which we play out our existence ripples into the future in ways we cannot imagine. Since the Gothic is also concerned with the blurring of boundaries such as those between the time and space continuum, the dead and undead, sanity and insanity, circumstances surrounding such events become the underpinning of this collection. Gothic narrative consistently jars social lethargy through the exposure of excessive behaviors and through an examination of the horrific. Hardwired is written through this lens as social commentary against patriarchal mores that devalue the feminine, cultural dominance that degrades native and immigrant populations, and religious and social institutions that perpetuate subjugation rather than promote respect. Woven throughout the collection is the verity, we are born to die. Gothic tradition advocates the importance of the supernatural --- a recognition that there is a force at play beyond our logic and rational. As a writer, I make use of this tradition to create stories in which the reader is presented with a fresh perspective on the miracle of their being and how their being serves the time and space continuum.
Keywords: Gothic; short stories